Based on the Zero Product Property, which of the following statements must be true about the quadratic equation (2x−3)(x+2)=0?

1 answer

Based on the Zero Product Property, the statement "if a product of two factors is equal to zero, then at least one of the factors must be equal to zero" applies.

In the case of the quadratic equation (2x−3)(x+2)=0, to satisfy the Zero Product Property, either (2x - 3) must be equal to zero or (x + 2) must be equal to zero.

Therefore, the following statements must be true:

1. 2x - 3 = 0
or
2. x + 2 = 0